A One-Pot, Multicomponent Synthesis of Trifluoromethylated Spiropiperidines under Catalyst-Free Conditions - Shi, Wei; Wang, Yang; Zhu, Yingjun; Zhang, Min; Song, Liping; Deng, Hongmei (Synthesis, 2016)
A convenient, efficient, one-pot strategy for the synthesis of structurally diverse trifluoromethylated spirotetrahydropyridine-3-carboxylate derivatives is disclosed by taking advantage of a four-component reaction involving arylidene isoxazol-5-ones, aromatic aldehydes, ethyl 4,4,4-trifluoro-3-oxobutanoate and ammonium acetate. Additionally, a more consecutive approach to the same products is achieved via a one-pot, multicomponent reaction. The protocol allows easy access to trifluoromethylated spiroheterocycles in moderate to good yields under mild and catalyst-free conditions.
Keywords: fluorinated heterocycles; Michael addition; spiropiperidines; catalyst-free; multicomponent reactions